1995
DOI: 10.4141/cjas95-066
|View full text |Cite
|
Sign up to set email alerts
|

Influence of processing on dietary enzyme effect and nutritive value of diets for laying hens

Abstract: Vukic Vranjes, M., pfirter, H. P. andWenk,C. lggs.Influence of processing on dietary enzyme effcc,t and nutritive value of diets for laying hens. Can. J. Anim. Sci. 75: 453460.Two experiments were carried out to examine the influence of aTrichodermaviride eniymecomplex [cellulase, endo-p-(l:3X1:4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…It is known that high temperatures during expander treatment can result in denaturation of proteins or destruction of feed additives such as enzymes which promote digestibility. Furthermore, interactions of high temperatures, moisture and sugar could result in the development of indigestible Maillard products [13,18,19]. These adverse effects on feed could also be responsible for the lower protein digestibility of expanded and pelleted feed compared to solely pelleted feed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that high temperatures during expander treatment can result in denaturation of proteins or destruction of feed additives such as enzymes which promote digestibility. Furthermore, interactions of high temperatures, moisture and sugar could result in the development of indigestible Maillard products [13,18,19]. These adverse effects on feed could also be responsible for the lower protein digestibility of expanded and pelleted feed compared to solely pelleted feed.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, the increase in ileal chyme viscosity is related to the damage of supplemented enzymes by the high processing temperatures. In studies by Inborr and Bedford [23] and Vranjes et al [19], markedly decreased enzyme activities were shown due to pelleting or extrusion. However, this effect was not observed when feeding coarsely ground, pelleted and expanded feed although equivalent processing temperatures were used.…”
Section: Discussionmentioning
confidence: 99%
“…However, and surprisingly, the enzyme treated diet still improved the energy and fat utilization in laying hens compared with the control. In a second experiment in the same study, 52% of the blend activity was lost after pelleting, however, enzyme improved nutrient utilization in unprocessed and pelleted diet to the same extent (109). Such observations might suggest the residual activity was still efficacious post-processing or initial enzyme dosing was excessive of available substrates.…”
Section: Feed Processing and Efficacy Of Exogenous Feed Enzymesmentioning
confidence: 97%
“…For example, effects of different pelleting temperatures 60, 70, 80, 90, and 100°C on the activity of fungal amylase and bacterial amylase added in barley, wheat and soybean diet suggested that fungal amylase can be pelleted at temperatures of up to at least 80°C and bacterial amylase up to 90°C without a considerable loss in analyzed activity (108). More than 65% of activity of a blend of cellulase, β-glucanase, and xylanase was lost in a barley, corn, dried grass, wheat bran, peanut meal and soybean meal diet subjected to extrusion (109). However, and surprisingly, the enzyme treated diet still improved the energy and fat utilization in laying hens compared with the control.…”
Section: Feed Processing and Efficacy Of Exogenous Feed Enzymesmentioning
confidence: 99%
“…Decréscimo na extratibilidade da fração lipídica tem sido citado por outros autores e observado mesmo após a hidrólise ácida (Guzman et al, 1992;Ho & Izzo, 1992;Vranjes et al, 1995), fato constatado neste trabalho para as proporções 25% soja e 100% milho. Uma possível explicação é a formação de complexos entre as frações amilose e lipídios, estáveis em hidrólise ácida (Haythornthwaite, 1986).…”
Section: Resultsunclassified